A New Protein Synthesis Factor from Escherichia coli - Kan, Yuet Wai (1970)
A new factor that effects protein synthesis by Escherichia coli extracts was partially purified from the 1 M NH(4)Cl wash of E. coli ribosomes. This factor stimulates the binding of aminoacyl-tRNA to 30S ribosomes, and it increases the rate of synthesis of polyphenylalanine in the presence of 30S and 50S subunits.